Link optimization strategy based on spectral moment in wireless sensor network - Qing-song CAI; Xi-hou CHEN (Tongxin xuebao)
In order to prolong the life of the wireless sensor network (WSN),an adaptive local communication link optimization algorithm of nodes was proposed to optimize the network structure dynamically.By introducing the term of Laplacian spectrum moment,each node can make the decision of adding or deleting a link iteratively with their neighborsusinglimited local network structural information,and then the whole network can evolve to a predefined structure.The experimental results show that each node takes only finite iterations and then the network structure can converge quickly to the target,which prove the effectiveness of the algorithm.